Dutch Colonization and Slavery of Asia: From Apology to Reparation - Steinmetz, Carl H. D. (Advances in Social Sciences Research Journal, 2024)
This article is about the history of forced apologies and reparations for the 350 years of Dutch colonization and the Dutch war of occupation of the Republic of Indonesia from 1945-1949, the trade in enslaved people, the extermination of the indigenous population, their replacement by people willing to serve the Dutch colonists, and the looting and plundering of natural mineral resources and earthly products such as nutmeg. The apologies issued are half-hearted, enforced by lawsuits that focus on a few rather than entire populations. The apologies are limited to the Republic of Indonesia and then only for the period 1945-1949. Currently, the Netherlands is considering apologies and possibly reparations for the suffering inflicted on Africans in the transatlantic triangle. In the process, Asian genocides, torture, executions, beheadings, enslavement of people, and looting and robbery of people and land are being covered up. Perhaps this is neo-colonization at its best. This article also makes a proposal, based on the insights of the international reparation’s movement and transitional justice, in the hope that the Netherlands and its Dutch municipalities will begin to mend their ways. At the heart of this proposal are methods for apologizing and repairing suffering. This can only be done together with our Asian sisters and brothers.